Aesthetic Literacy in Young People’s and Adults’ Awareness From a Developmental Learning Perspective - Cunha de Araújo, Gustavo; Carlos Miguel, José [UNESP]; Gomes de Araújo, Rosane (Frontiers, 2021)
In Brazilian schools, many teachers do not organize their teaching and students’ tasks and actions in a way that facilitates theoretical thinking based on the abstraction and generalization of the work content. Because many students struggle to accomplish the tasks and actions themselves, teachers guide them. Over time, the students begin to have more autonomy in executing the proposed activities, as they completed mental operations while learning. This article aims to investigate how young people’s and adults’ awareness of the countryside is formed based on visual elements and writing, facilitating an understanding of their reality. A didactic–formative experiment was performed based on the cultural–historical theory. The comic books produced by the participants allowed them to develop their overall thinking, moving from the abstract to the concrete. They also formed an awareness of reality, which allowed them to have greater autonomy in the production of these stories as a means of representation and transformation of reality.
Keywords: aesthetic literacy; comic books; developmental learning; rural education; study activity